Identifying the oxygen evolution mechanism by microkinetic modelling of cyclic voltammograms. (1st June 2021) - Geppert, Janis; Kubannek, Fabian; Röse, Philipp; Krewer, Ulrike
Highlights: For the first time microkinetics on hydrous iridium are studied based on modelling. The coverages of surface intermediates are quantified over a wide potential range. Slow water adsorption leads to reduced surface states even at high potentials during the oxidation reaction. Abstract: Electrocatalytic water splitting is currently one of the most promising reactions to produce "green" hydrogen in a decarbonized energy system. Its bottleneck reaction, the oxygen evolution reaction (OER), is catalysed by hydrous iridium, a stable and active catalyst material. Improving the OER requires a better and especially quantitative understanding of the reaction mechanism as well as its kinetics. In this work, we present an experimentally validated microkinetic model that allows to quantify the mechanistic pathways, emerging surface species prior and during the OER, the reaction rates for the single steps and essential thermodynamic properties. Therefore, two mechanisms based on density functional theory and experimental findings are evaluated on which only simulation results of the theory-based one are found to be in full accordance with cyclic voltammograms even at different potential rates and, thus, able to describe the catalytic system. The simulation implies that oxygen is evolving mostly via a fast single site pathway ( * OO → * + O 2 ) with an effective reaction rate, which is several orders of magnitude faster compared to the slow dual site ( 2 * O → 2 * + O 2 ) pathway rate. Intermediate states of roughly 7% Ir(III), 25% Ir(IV) and 63% Ir(V) are present at typical OER potentials of 1.6 V vs RHE. We are able to explain counterintuitive experimental findings of a reduced iridium species during highly oxidizing potentials by the kinetic limitation of water adsorption. Although water adsorption is in general thermodynamically favourable, it is kinetically proceeding slower than the electrochemical steps at high potential. In the lower potential range from 0.05 to 1.5 V vs RHE the stepwise oxidation of the iridium is accompanied with van der Waals like ad- and desorption processes, which leads in comparison to Langmuir-type adsorption to a broadened peak shape in the cyclic voltammograms. Overall, our analysis shows that the dynamic microkinetic modelling approach is a powerful tool to analyse catalytic microkinetics in depth and to bridge the gap between thermodynamic calculations and experiments.